Visualizing the Growth of Electric Vehicles (2010–2024) using Power BI: A Data-Driven Insight - Rizaldi Putra Sonjaya; Mochammad Zulvikri; Muhammad Thoriq Fadhlurohman; Akhmad Bakhrun (SAINTIS Publishing, 2025)
This study investigates the surge in global electric vehicle (EV) adoption from 2010 to 2024 by utilizing Power BI as a data visualization tool. The research problem centers on the lack of integrated, real-time visual analysis that captures temporal trends, regional disparities, and powertrain diversity within EV markets—particularly in developing countries. Using a descriptive quantitative method, this study employed four main stages: data collection, processing, visualization, and interpretation. Data was sourced from the Kaggle platform and processed using Power BI’s star-schema model. The result is an interactive dashboard that allows users to explore EV data across drivetrain types, parameters (sales, stock, share), regions, and years. The findings highlight a sharp increase in EV sales between 2020 and 2023, with significant adoption in the USA, China, and Europe. Conversely, Southeast Asia, including Indonesia, remains limited by infrastructural and economic challenges. The study demonstrates that BEVs dominate market share, while FCEVs remain in the early adoption stage. By integrating visual elements such as slicers, KPIs, and trend graphs, Power BI enables deeper analysis and informed decision-making. The implications of this study are relevant for policymakers and industry leaders seeking real-time, actionable insights to guide EV adoption strategies in various regions.